Prognostic value of t(4;14) translocation in newly diagnosed multiple myeloma patients in novel agent era. Issue 1 (31st December 2023) - Geng, Chuanying; Yang, Guangzhong; Zhou, Huixing; Wang, Huijuan; Li, Yanchen; Leng, Yun; Zhang, Zhiyao; Jian, Yuan; Chen, Wenming
ABSTRACT: Objective: To evaluate the prognostic value of t(4; 14) translocation for newly diagnosed multiple myeloma (MM) patients in the novel agent era. Methods: We retrospectively analyzed 606 newly diagnosed MM patients treated with novel agents. The propensity score matching technique was used to reduce the bias between groups. Results: Among 606 patients, t(4; 14) was observed in 108 (17.8%) patients, among which 79 (73.1%) were accompanied by 1q21 gain and/or del 17p. Median overall survival (OS) (56.2 vs. 87.3 months) and progression-free survival (PFS) (25.7 vs. 37.6 months) were significantly shorter in patients with t(4;14) compared with patients without cytogenetic abnormalities. Univariate Cox proportional hazards regression analysis showed that the t(4;14) was not associated with shorter OS ( p  = 0.666) and PFS ( p  = 0.164). The multivariable analysis also showed t(4;14) was not a poor prognostic factor for OS and PFS of patients with newly diagnosed MM ( p  > 0.05). After balancing the distribution of factors between patients with and without t(4;14) by the propensity score matching technique, patients with t(4;14) had similar OS (57.6 vs. 56.5 months, p  = 0.964) and PFS (26.5 vs. 28.1 months, p  = 0.740) with the patients without t(4;14). Conclusions: These results demonstrated that t(4; 14) alone may be not a poor prognostic factor patients with newly diagnosed MM in the novel agent era.